الشعر العربي الحديث في نيجيريا بين الوزير جنيد وعيسى ألبي : تحليل ونقد وموازنة - عبد الله، محمد جامع (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This research work attempts a comparative analysis of Arabic poetic works which are produced by a Muslim scholar of the northern origin (Hausa) and a Muslim scholar of southern origin (Yoruba) in Nigeria. As a case study, it chooses Waziri Junaidu, a Hausa scholar and Isa Alabi, a Yoruba scholar, because of the significant quality and originality of their poems. This research employed three approaches: historical, analytical and comparative, which unlocked some historical facts on the development of Arabic poems in the two regions, and also attempted phenomenal and characteristic analysis of the selected literary models in an effort at identifying the similarities and differences in them. This study thus underscores the positive roles Islam has played in the emergence and maturation of Arabic poetry in both regions. It also highlights some prominent Arabic poets and their poems, and then analytically addresses the form and contents of Waziri Junaidu's and Isa Alabi's odes, by way of comparison, in an attempt to highlight the areas of differences and similarities inherent in them. In conclusion, the study discovers that both poets are comparably outstanding. However, Waziru Junaidu is seen more of a poet, scholar and historian while Isa Alabi, in addition, has a more comprehensive and holistic view on life issues. As such, the researcher recommends that more studies on the Arabic poems of other Arabic poets should be carried out in order to reveal various areas of interdependency between the two regions.